2007
DOI: 10.1007/s00261-007-9306-1
|View full text |Cite
|
Sign up to set email alerts
|

Do all non-calcified echogenic renal lesions found on ultrasound need further evaluation with CT?

Abstract: From the surprisingly limited evidence available in the literature, it must be concluded that all non-calcified echogenic renal lesions detected with ultrasound need a CT to rule out an RCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 7 publications
2
19
0
Order By: Relevance
“…In summary, the results of this study strongly suggest that a small echogenic renal mass up to 1 cm in size that is incidentally discovered sonographically has such a low prevalence of malignancy, current or future, that it can be ignored if it fulfills the following study criteria: (1) there is no history of malignancy or presence of a known mass elsewhere that might be malignant; (2) more than 50% of the mass is echogenic by visual estimation; (3) the mass is intracortical, visually extending less than 50% from the cortex either peripherally or into the renal sinus; (4) the maximum diameter can be measured in 3 orthogonal planes on axial and longitudinal sections; and (5) the patient is an adult.…”
Section: Discussionmentioning
confidence: 98%
“…In summary, the results of this study strongly suggest that a small echogenic renal mass up to 1 cm in size that is incidentally discovered sonographically has such a low prevalence of malignancy, current or future, that it can be ignored if it fulfills the following study criteria: (1) there is no history of malignancy or presence of a known mass elsewhere that might be malignant; (2) more than 50% of the mass is echogenic by visual estimation; (3) the mass is intracortical, visually extending less than 50% from the cortex either peripherally or into the renal sinus; (4) the maximum diameter can be measured in 3 orthogonal planes on axial and longitudinal sections; and (5) the patient is an adult.…”
Section: Discussionmentioning
confidence: 98%
“…9,10 Large (>1 cm) echogenic renal cortical nodules can be further characterized with CT to confirm the presence of intratumoural fat. 5,9 The management of small (<1 cm) echogenic renal cortical nodules varies and is controversial. 5 A meta-analysis on the topic concluded that, based on limited evidence, all incidental echogenic cortical nodules should be further characterized with CT. 9 CT is limited for the detection of fat within small (<1 cm) nodules because of inaccurate placement of region of interest (ROI) measurements and volume averaging of voxels containing renal parenchyma and fat.…”
Section: Diagnosis Of Aml Is Difficult When the Tumour Is Smallmentioning
confidence: 99%
“…5,9 The management of small (<1 cm) echogenic renal cortical nodules varies and is controversial. 5 A meta-analysis on the topic concluded that, based on limited evidence, all incidental echogenic cortical nodules should be further characterized with CT. 9 CT is limited for the detection of fat within small (<1 cm) nodules because of inaccurate placement of region of interest (ROI) measurements and volume averaging of voxels containing renal parenchyma and fat. 5 Thin-section CT 6 can increase the diagnostic yield ( Fig 3); however, for very small nodules CT is frequently non-diagnostic even when pixel analysis is performed.…”
Section: Diagnosis Of Aml Is Difficult When the Tumour Is Smallmentioning
confidence: 99%
“…Analyses were performed by the same blinded radiologist. For US, echogenicity of the AML was assessed with respect to adjacent renal CP (as described previously [26,27]) as hypoechoic (echogenicity<CP), isoechoic (echogenicity similar to CP), or hyperechoic (echogenicity>CP).…”
Section: Us and Mri Analysismentioning
confidence: 99%